Jamāl Al-Kināyah Fī Burdah Ka‘B Ibn Zuhayr: Dirāsah Taḥlīliyyah - Abdul Wahab Nafan; Andri Warseto Naf'an (Journal of Arabic Literature (JaLi), 2025)
This study examines the aesthetic and rhetorical dimensions of kināyah (metonymic allusion) in the Burdah by Kaʿb ibn Zuhayr, a celebrated poem recited before the Prophet Muhammad ﷺ as an act of repentance and acceptance of Islam. Unlike previous studies that focused on the poem’s general literary, historical, and symbolic aspects, this research treats kināyah as an independent subject of analysis to uncover its functional role in constructing poetic meaning. Employing a qualitative descriptive-analytical approach, the study analyzes the original text alongside classical commentaries and modern scholarship. The findings reveal that kināyah in the poem manifests predominantly in two forms: kināyah of the attribute (al-ṣifah) and kināyah of the described (al-mawṣūf), while kināyah of ratio (al-nisbah) is absent. The analysis identified 30 instances of kināyah of the attribute, significantly outnumbering the 13 instances of kināyah of the described. The poet utilizes these devices strategically; dedicating twenty verses to the she-camel through kināyah of the described to symbolize psychological endurance , while employing kināyah of the attribute to extol the Prophet and the Emigrants (Muhajirun) with qualities of nobility, bravery, and restraint in victory. The study concludes that kināyah in Kaʿb’s Burdah functions as more than a rhetorical ornament; it serves as a profound artistic tool that bridges pre-Islamic imagery with Islamic values, enriching the poem's emotional depth and confirming its enduring place in Arabic literary heritage